Leveraging Technology in Education: The Impact of Gitmind Mindmapping on Social Studies Learning - Hidayatullah, Raza Syarif; Zaharah, Zaharah (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2024)
This study uniquely examines the impact of globalization on education in Indonesia, specifically focusing on the integration of technology into learning environments. In light of the increased use of technology, many students are experiencing decreased concentration and interest in learning due to its excessive and uncontrolled use. Additionally, a significant number of teachers and lecturers exhibit low technological literacy, resulting in the continued use of outdated teaching methods. Utilizing a descriptive quantitative methodology with a simple random sampling technique, the research involved 125 Social Science students from the 2021 cohort at the Jakarta State Islamic University. Data were collected through Google Form questionnaires post-Final Semester Examination, along with observations and literature reviews, and analyzed using SmartPLS software. The findings revealed that integrating the mind mapping method via the Gitmind application significantly enhanced students' learning outcomes in Social Studies, highlighting the need for updating learning media, methods, and strategies to align with technological advancements. This study underscores the critical need for educational reform in Indonesia, advocating for a transition from traditional teaching practices to more innovative, technology-driven approaches. The successful use of Gitmind suggests that such tools can substantially improve student engagement and learning efficacy. The implications of this research extend beyond the Social Science curriculum at Universitas Islam Negeri Jakarta, proposing that similar technological integrations could benefit various subjects and disciplines across other universities. This contribution to educational development underscores the importance of creative and effective learning approaches suitable for the digital era, potentially serving as a model for broader educational reforms.